The Effect of Normative Feedback on Throwing Aiming Task Learning in 9-11-Year-Old Children - Hamide Jahanbakhsh; Parvane Shafienaya; Seyede Nahid Shetab Booshehri (University of Tehran, 2015)
Normative feedback is a kind of feedback which involves information about an individual's performance in comparison with other peers unrealistically (positive or negative). The aim of the present study was to determine the effect of normative feedback on throwing aiming task learning in children aged between 9 and 11 in Ahvaz city. For this purpose, 90 right-handed children were selected with convenience method as the statistical sample and were divided into three groups (each group 30 subjects) of positive normative feedback, negative normative feedback and control based on their age, height, weight, hand length, arm length and pretest scores. Acquisition phase included 6 blocks of 10 trials. In this phase, all groups received real feedback after each trial and positive and negative normative groups received normative feedback after each block in addition to real feedback. The transfer and retention tests were carried out immediately and after (delayed) the acquisition phase respectively. After checking the data normality and homogeneity of variances, data were analyzed with one-way ANOVA with repeated measures, one-way analysis of variance, and Bonferroni post hoc test (P≤0.05). There were significant differences in all three phases among the three groups and positive normative feedback group showed better performance (P=0.001). The findings showed that positive normative feedback had a facilitating effect on motor learning.